THE EFFECTIVENESS OF MATH LEARNING USING COOPERATIVE LEARNING MODEL TYPE OF MAKE A MATCH ON STUDENTS MATHEMATICS LEARNING OUTCOMES IN GRADE VIII - Dwi Febriani Sumiartini; Sunaryo Sunaryo (Universitas Ahmad Dahlan, 2018)
The low student learning outcomes are influenced by several factors, one of which is the model used in the less varied learning of mathematics still centered on the teacher. This study aims to determine more effective learning between mathematics learning using the cooperative learning model type to match mathematics learning using a direct learning model to students' mathematics learning outcomes. The population in this study were all eight grade students of Muhammadiyah Junior High School 2 Kalasan (SMP Muhammadiyah 2 Kalasan) in Academic Year 2016/2017, which consists of 5 classes. The sampling technique using a random sampling class and selected VIII E as an experimental class and VIII C as a control class. The data was collected used in the test method. Instrument testing used validity and reliability test. Data analysis techniques used for the analysis include the prerequisite test, normality test, and homogeneity test. To test the hypothesis in this study, a two-party t-test and one-party t-test with a significant level of 5% were tested. Based on mathematics learning result obtained that 1) tcount = 4,2948 and ttable = = 2,0650 which means > . This means that there is a difference in learning outcomes between learning mathematics using a cooperative learning model type. It makes a match with mathematics learning using a direct learning model of eight grade students of Muhammadiyah Junior High school 2 Kalasan (SMP Muhammadiyah 2 Kalasan) of even semester in Academic Year 2016/2017. 2) Â tcount = 4,2948 and ttable = = 1,7116 which means tcount Â > . This shows that the learning of mathematics with the cooperative learning model type make a match is more effective than the learning of mathematics using direct learning model towards mathematics learning outcomes in eight grade students of SMP Muhammadiyah 2 Kalasan of even semester in Academic Year 2016/2017.